Distributed output feedback control of two-time-scale hyperbolic PDE systems - Christofides, Panagiotis D.; Daoutidis, Prodromos (Zielona Góra: Uniwersytet Zielonogórski)
This article focuses on systems of two-time-scale hyperbolic partial differential equations (PDEs), modeled in singularly perturbed form, for which the manipulated inputs, the controlled and the measured outputs are distributed in space. The objective is to synthesize distributed output feedback controllers that guarantee closed-loop stability and enforce output tracking, provided that the speed ratio of the fast versus the slow dynamical phenomena of the two-time-scale system is sufficiently large. Initially, singular perturbation methods are used to derive two separate PDE models which describe the fast and slow dynamics of the original system.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka